ANALYSIS OF SERVICE QUALITY ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION AT THE X CLINIC LABORATORY IN PEMATANG SIANTAR - Ramauli, Juliana; Sibarani, Mentiana (International Journal of Social Service and Research, 2024)
The health industry in Indonesia faces a variety of complex and multidimensional challenges. In the face of fierce competition from hospitals that offer self-contained laboratory services and the development of infrastructure that facilitates access to more well-equipped healthcare facilities, it is important to understand how service quality affects customer satisfaction and loyalty. This study aims to explore the influence of Service Quality on Customer Satisfaction and Customer Loyalty at the X Clinical Laboratory in Pematang Siantar City, as well as to examine the role of customer satisfaction as a mediator. The results show that Service Quality has a significant positive influence on customer satisfaction (coefficient: 0.8825), indicating that an improvement in Service Quality will increase customer satisfaction. Based on these findings, the management of Clinical Laboratory X is advised to implement several strategies to improve service quality, customer satisfaction, and loyalty to remain the top choice.